What are citizens' concerns in urban regeneration? Exploring critical factors for participatory intention, a case from Shanghai - Li, Yuan; Wei, Qin; Guo, Jianhao; Song, Yanran; Wu, Xingyao (Frontiers in Psychology, 2025)
Urban regeneration is a global concern and a crucial component of China's recent urbanization efforts. Among the several stakeholders, citizens' participatory intention in the urban regeneration is closely related to a city's sustainable development. Given China's top-down governance tradition, encouraging public participation has been a challenge for the government. To understand what citizens really care in urban regeneration, this study employed a research model based on theories of planned behavior, place attachment, and place memory, to examine citizens' behavior, focusing on how different variables influenced their participation. The Nanjing West Road Historic and Cultural Area (NWRHCA) in Shanghai has been selected as a case study. Data were collected from 1,137 valid questionnaires, and structural equation modeling (SEM) was applied to test 10 hypotheses regarding the effect paths from six variables to behavioral intention and performance. Additionally, we conducted in-depth interviews to further explain the SEM analysis results. The findings indicate that: (1) place attachment is an important factor in shaping citizens' intention to participate; (2) there are significant negative correlations between attitude and behavioral intention, as well as between memorable urban experiences and behavioral intention; (3) conflicts among stakeholders impede public participation in urban regeneration and (4) willingness of citizens' participation can be enhanced through a “step-by-step” procedural approach, the institutionalization of regeneration process, and the cultivation of residents' place attachment. These findings provided new insights into the conventional approach to urban regeneration in China, exploring citizens' core interest, and highlighting important implications for facilitating diverse forms of public participation in future urban regeneration.